Pendekatan Metode Bermain: Upaya Meningkatkan Hasil Pembelajaran Lari Sprint pada Siswa di MI Negeri 1 Gunungkidul - Yuwanto, Yuwanto (Jurnal Pendidikan Madrasah, 2023)
This study aims to improve sprint learning through a play approach. This study is classroom action research. The subjects of the study were 23 students of grade V MIN 1 Gunungkidul for the 2023/2024 academic year, consisting of 12 female students and 11 male students. The data collection method used in this study was using observation sheets and questionnaires, conducted by researchers and collaborators. The results showed that the playing approach can improve sprint learning for class V. Based on the results of the questionnaire, it was seen that activity, attitude and cooperation were categorized as good, while the evaluation results in cycle 1 amounted to 60.87% of students who were able to do sprint movements correctly, in cycle 2 increased to 78.26% of students who were able to do sprint movements correctly.